Uji Efek Antiartritis Ekstrak Etanol 80% Kulit Buah Delima Merah (Punica granatum L) Terhadap Udem Pada Telapak Kaki Tikus Putih Jantan yang diinduksi oleh Complete Freund’s Adjuvant - Sari, Rusmalita Pebriana; Amin, Juheini; Sari, Santi Purna (Majalah Ilmu Kefarmasian, 2010)
Rheumatoid arthritis is a chronic inflammatory disease that can degrade the quality of patient survival. Conventional treatments of this disease have potentially dangerous side effects. Therefore, many patients are turning to alternative medicine using medicinal herbs, one of which is the fruit of Punica granatum L. The aim of this research was to determine antiarthritis effect of 80% ethanolic extract of Punica granatum L. fruit peel which had been given orally on 17-30th day based on decreased edema volume and percentage indexes of arthritis. The method was adjuvant induced arthritis by using the complete freund’s adjuvant 0,1 mL by subplantar and allowed to arthritis until day 16. The animals test were used 33 male rats of Sprague Dawley strain that were divided into six groups: normal control, positive control, negative control, and three groups had received suspension of 80% ethanolic extract of Punica granatum L. fruit peel in 0,5% CMC at doses 20, 40, and 80 mg/200 g body weight. The Edema volume was measured by pletismometer on days 17, 20, 23, 26, 29, 31 and indexes of arthritis determined on days 17 and 31. The Results showed that they were not significant difference in the decreased edema volume and the percentage indexes of arthritis, although the percentage inhibition of edema elevated with increasing dose.